The Crime of Land Grabbing from a Criminological Perspective - Ahmad, Moh. Nur Sidik; Puluhulawa, Moh. R. U; Achir, Nuvazria (Universitas Negeri Gorontalo, 2024)
This research aims to determine the factors behind the criminal act of land grabbing in the jurisdiction of the Gorontalo Regional Police. The type of research used is empirical legal research with a qualitative approach. The results of the research show that the factors behind the occurrence of criminal acts of land grabbing in the jurisdiction of the Gorontalo Regional Police are; Firstly, economic problems that force someone to commit acts of seizing and taking away the rights of other people, whether they are close or related or not. Second, the condition of abandoned land, namely people's ignorance of the assets they own. Third, lack of legal awareness, and fourth, land remains fixed while the population increases, which indicates a condition where population growth is increasingly rapid so that numbers increase and production of fixed land areas even decreases. Conflicts in the land sector are driven by interests so one of the parties even commits criminal acts in the land sector.